Adolescents’ Mental Health Efforts in the Implementation of Worship - Munaya Fauziah; Nurmalia Lusida; Ernyasih Ernyasih; Fini Fajrini; Dadang Herdiansyah (Fakultas Kesehatan Masyarakat Universitas Muhamamdiyah Jakarta, 2022)
Mental health is a person's mental health condition. Someone who has a healthy soul if the mind, feelings, and physically are also healthy. One of the most effective ways to overcome mental disorders is to carry out worship. In addition, by carrying out worship, you can also get a double reward from Allah SWT. According to the results of Riskesdas 2018, it shows that mental disorders have occurred starting at the age (adolescents 15-27 years) with a prevalence of 6.2%. In Indonesia, currently, the incidence of mental disorders is around 1 in 5 of the population, of which about 20% of the population has the potential to experience mental disorders. The purpose of this study was to examine some of the literature on mental health in adolescents in worship. This study uses a literature review method where the researcher conducts a series of studies involving various kinds of information from the literature such as journals and theses. The results of research from various literary sources show that Islam has regulated in such a way both in the implementation of worship and in maintaining human life through good mental health. It can be concluded that Adolescents who want to have a healthy mental mindset must be good, in other words, their worship is devoted, intend everything because of Allah SWT.